Development of maja blanca mix powder - Almendras, Jennifer Eusebio; Luna, Myrna Benita Z. (2002., 2002)
ABSTRACT The study aimed to develop a maja blanca mix powder. In Phase 1, the formulation of Daza (1974) was selected as the reference sample based on the acceptability and physico-chemical tests of 4 existing maja blanca formulations. Phase 2 involved the conversion of the reference formulation to a mix powder by substituting 64% coconut milk extract with 35% commercially available coconut cream powder. Briefly, the preparation of maja blanca from the developed mix powder involved dispersion, simultaneous heating and mixing, molding and cooling. In Phase 3, the formulation and process for the developed product was standardized. The microbiological, physico-chemical and sensory characteristics of the resulting product from 2 bench scale production runs did not significantly vary (p>0.05). A 96 g unit pack of the developed product costs Php 18.62.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Convenience foods; Snack foods